2022
DOI: 10.5009/gnl210290
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic Burden Determines Cardiovascular Risk among Subjects with Metabolic Dysfunction-Associated Fatty Liver Disease

Abstract: Background/Aims: Metabolic dysfunction associated fatty liver disease (MAFLD) has recently been introduced to compensate for the conventional concept of nonalcoholic fatty liver disease (NAFLD). We explored whether fibrotic burden determines the risk of atherosclerotic cardiovascular disease (ASCVD) among subjects with MAFLD.Methods: We recruited 9,444 participants from the Korea National Health and Nutrition Examination Survey (2008 to 2011. Liver fibrosis was identified using the fibrosis-4 (FIB-4) index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…High fibrotic burden in patients with FLD is a major risk factor for developing HCC and liver-related mortality, 27,28 and other studies have shown that a high fibrotic burden in liver is independently associated with an increased CVD risk in patients with FLD. 16,17,19 Based on these findings, it might be suggested that no MAFLD group with the lowest fibrotic burden in our study might have the lowest risk of HCC, liver-related mortality, and CVD, although additional longitudinal or mechanistic analyses were not performed. Second, in our study, DM-MAFLD had the highest risk of advanced liver fibrosis.…”
Section: Discussionmentioning
confidence: 83%
“…High fibrotic burden in patients with FLD is a major risk factor for developing HCC and liver-related mortality, 27,28 and other studies have shown that a high fibrotic burden in liver is independently associated with an increased CVD risk in patients with FLD. 16,17,19 Based on these findings, it might be suggested that no MAFLD group with the lowest fibrotic burden in our study might have the lowest risk of HCC, liver-related mortality, and CVD, although additional longitudinal or mechanistic analyses were not performed. Second, in our study, DM-MAFLD had the highest risk of advanced liver fibrosis.…”
Section: Discussionmentioning
confidence: 83%
“…Given the metabolic hallmark of the new definition of MAFLD, it could be speculated that an increased risk of cardiovascular complications should be expected in this subtype of NAFLD [37]. Indeed, despite data about cardiovascular abnormalities in MAFLD are limited, it has been showed that individuals with MAFLD phenotype had a substantially increased ASCVD risk compared to those without MAFLD [38]. However, while the new MAFLD definition better outlines the syndromic of NAFLD and encloses the large majority of fatty liver patients, it excludes those with metabolic-healthy NAFLD, that could be probably considered as the "pure" genetic ones [39].…”
Section: The Intricate Relationship Between Nafld and Cardiometabolic...mentioning
confidence: 99%
“…Furthermore, the TyG index was associated with a higher risk of CAP among those with MAFLD, suggesting that MAFLD may enhance the effect of TyG index on the risk of CAP. A recent study indicated that individuals with MAFLD had a substantial ASCVD risk compared to those without MALFD [37]. Thus, our ndings might provide clinical implications for applying identi cation and intervention for subjects with higher TyG index and MAFLD, which may prevent the risk of CAP.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies indicated that railway workers were more likely to have a high incidence of the metabolic disease due to their association with poor lifestyle behaviors and irregular work schedules. As one of the metabolic diseases, MAFLD, a novel concept proposed by an international consensus in 2020, was mainly related to insulin resistance and as a risk factor for ASCVD, and the TyG index was a potential risk factor for MAFLD [34][35][36][37][38]. Moreover, scienti c evidence has shown that lifestyle including physical activity, dietary pattern, salt intake, etc., improved cardiovascular disease markers effectively [39,40].…”
Section: Discussionmentioning
confidence: 99%